Razvijanje računalniškega mišljenja z in brez robotov v predšolskem obdobju - Ferčec, Karmen (Revija inovativna pedagogika, 2025)
Many computational thinking activities were implemented to liven up the daily activity schedule and help children better cope with life's challenges and problems. First, computational thinking skills were developed through entertaining play-based activities that required children to orient themselves on a grid in the playroom and a paper sheet. Second, the children were introduced to the basics of coding by moving around while following their partner's instructions or according to the given algorithms. Afterward, the children became acquainted with the robots Bee Bot and M-Tiny. The children were closely observed throughout the activities. The children were highly motivated, attentive, and eager to learn during these computational thinking activities. We found that the mTiny robot is easier to use than the Bee bot, so we offered the Bee bot robot to children who solve problems independently. In contrast, we provided the mTiny robot for children who need an adult to help them solve problems. We believe that children need more activities like this to develop the ability to solve problems independently.
Keywords: algorithms; algoritmi; computational thinking; cooperative learning; predšolska vzgoja; Predšolsko učenje in poučevanje; pre-school education; problem-solving; računalniško mišljenje; reševanje problemov; Robotika; sodelovalno učenje